BP Blowout : Inside the Gulf Oil Disaster - Jacobs, Daniel (Book collections on Project MUSE., 2016)
BP Blowout is the first comprehensive account of the legal, economic, and environmental consequences of the disaster that resulted from the April 2010 blowout at a BP well in the Gulf of Mexico. The accident, which destroyed the Deepwater Horizon oil rig, killed 11 people. The ensuing oil discharge--the largest ever in U.S. waters--polluted much of the Gulf for months, wreaking havoc on its inhabitants and the environment. A management professor and former award-winning Justice Department lawyer responsible for enforcing environmental laws, Daniel Jacobs tells the story that neither BP nor the federal government wants heard: how the company and the government fell short, both in terms of preventing and responding to the disaster. Critical details about the cause and aftermath of the disaster have emerged through court proceedings and with time. The key finding of the federal judge who presided over the civil litigation was that the blowout resulted from BP's gross negligence. BP has paid tens of billions of dollars to settle claims and lawsuits. The company also has pled guilty to manslaughter in a separate criminal case, but no one responsible for the tragedy is going to prison. BP Blowout provides new and disturbing details in a definitive narrative that takes the reader inside BP, the White House, Congress and the courthouse. This is an important book for readers interested in the environment, sustainability, public policy, leadership, and risk management.